(untitled) (Research, Society and Development, 2021)
Objective. The present systematic review aims to evaluate the available literature on the risk association between periodontitis and preeclampsia. Methodology. A search was carried out for scientific articles that studied the association between periodontitis and preeclampsia, the MEDLINE (PubMed) and Scopus platforms were used as search engines, case-control studies were selected that reported results such as the OR (Odds ratio), clear definitions and appropriate diagnostic criteria for periodontitis and preeclampsia. The review was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta analysis) guidelines. In addition, the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement was used to control the quality of the included studies. Results. Applying the inclusion and exclusion criteria, 15 case-control studies were obtained and included in the review. Of the 15 included studies, 13 (86.67%) showed a positive association between periodontitis and the development of preeclampsia. Age, parity, and smoking were the most controlled variables in each study. Conclusion. Periodontitis was a risk factor for preeclampsia, emphasizing the importance of periodontal care in prenatal programs. Systematic review registration: PROSPERO CRD42020205855.